Separation of the Messenger RNAs of Newcastle Disease Virus by Gel Electrophoresis - Collins, Bonnie Spanier (1973)
We have separated the 18-22S putative messenger RNA of Newcastle disease virus into seven species ranging in molecular weight from 0.55 to 1.53 × 10(6) using sodium dodecyl sulfate-acrylamide-gel electrophoresis at relatively high concentrations of acrylamide and for a relatively long time. Studies of the number and molecular weights of the proteins and the 18-22S RNAs of the virus suggests that these RNAs are in the right molecular weight range to code for the known proteins of Newcastle disease virus. In preliminary studies using this separation technique, we have demonstrated that: (a) there is no difference between the 18-22S RNA made during a normal infection and when genome replication is blocked; and (b) there is a strain-specific difference between the RNAs of Newcastle disease virus-AV and Newcastle disease virus-HP.